Witnessing a wounded world: a theology of ecological trauma - Middleton, TA (2022)
This thesis lies at the intersection of ecotheology and trauma theology. My basic claim is that the approach of Christian trauma theologians to cases of traumatic human suffering can be fruitfully extended and applied by ecotheologians in the context of the present ecological crisis. The category of trauma acknowledges the seemingly incomprehensible severity and scale of current ecological suffering, whilst also resisting the impulse to explain such suffering in terms of its origin or its solution. I argue that three defining characteristics of human trauma are identifiable in the ecological realm--namely, a rupture to communication, a rupture to flesh, and a rupture to time. But this ascription of trauma to nonhuman entities does not require envisaging the earth as conscious. Instead, I understand ecological trauma as an anthropomorphism of earth systems and processes that enables us to better relate to ecological suffering. Following existing work in trauma theology, I propose that the practice of bearing witness to ecological trauma constitutes a vital coping strategy. In response to the rupture of communication, I argue that Christ serves as a witness to traumas such as climate change and biodiversity loss. In response to the rupture of flesh, I expand this model of Christic witnessing by suggesting that Christ's incarnation in the flesh enables him to bear witness to the wounded flesh of the world. And in response to the rupture of time, I contend that Christ's recapitulation of creation, along with the persistence of the wounds on his resurrection and ascension flesh, allow him to witness the recurrence and permanence of contemporary ecological devastation. I conclude that a process of Christic witnessing forms one possible theology of ecological trauma. In short, Christ's permanently wounded flesh bears witness to a permanently wounded world.